2007
DOI: 10.1590/s0100-40422007000800020
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e validação de metodologia de análise de misturas biodiesel: diesel utilizando cromatografia gasosa-espectrometria de massas

Abstract: . The aim of this work was to develop and validate a method of analysis of biodiesel:diesel blends using HRGC-MS in SIM mode. The proposed method is applicable to biodiesel from linoleic oils, such as soybean oil. The following results were obtained: linearity over the methyl linoleate concentration range of 250-2500 mg L -1 (R 2 > 0.999); limits of detection and quantification of 2 and 5 mg L -1 , respectively; recovery from 82 to 96% of biodiesel in diesel and repeatability < 2% (RSD). Comparison between two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 6 publications
0
8
0
4
Order By: Relevance
“…Gas chromatography with flame ionization detector (GC-FID) or coupled to mass spectrometry (GC-MS) has been the most common techniques for determination of methyl esters in biodiesel [7,24].…”
Section: Analysis Of Fatty Acids Of the Biodiesel By Gc-fidmentioning
confidence: 99%
“…Gas chromatography with flame ionization detector (GC-FID) or coupled to mass spectrometry (GC-MS) has been the most common techniques for determination of methyl esters in biodiesel [7,24].…”
Section: Analysis Of Fatty Acids Of the Biodiesel By Gc-fidmentioning
confidence: 99%
“…Biodiesel, produced by the transesterification or esterification of vegetable or animal oils and fats or fatty acids, in the presence of an alcohol such as methanol or ethanol, [1][2][3] is one of the most promising alternative fuels. Besides being renewable, nontoxic and biodegradable, biodiesel can be added to petrodiesel due to its similar physico-chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…17 In the literature, many studies have demonstrated that the GC technique can be applied to determine the content of FAME or FAEE in samples of B100 or in mixtures of diesel and biodiesel, 19 and it is also used to quantify other substances like the alcohol used in the reaction and also secondary products such as glycerol, monoacylglycerides, diacylglycerides and triacylglycerides. 1,2,[20][21][22][23][24][25][26][27] However, due to the variety of raw materials 28,29 that can be employed for biodiesel production and the importance of its production in several countries, it is strategic to develop fast 30 and economically attractive methods, through modifications such as applying different column temperatures and lengths and the use of a different internal standard 23 exhibiting similar characteristics, but not present in biodiesel composition.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of these equations in monitoring the yield of transesterification with methanol is evident from their appearance in several works [17][18][19][20]. Correlations with NMR approaches have been studied in the monitoring of progressive transesterification of soybean and rapeseed oils only.…”
Section: Introductionmentioning
confidence: 99%